Integration of modern architecture in the development of culinary tourism in bili-bili through social behavior theory analysis - Armi Indrayuni; Shermina Oruh; Andi Agustang; Muh.Kamil (SEAN Institute, 2024)
This comprehensive study explores the development of culinary tourism at the Bili-Bili Reservoir in Gowa Regency, with a special focus on integrating modern architecture into the rich tapestry of local culture and environment. The research adopts a dual approach, employing SWOT analysis and social behavior theory, to gain a multifaceted understanding of visitor dynamics and environmental interactions. This qualitative study is grounded in extensive interviews with a diverse group of stakeholders, including tourists, local vendors, regional government officials, and members of the surrounding community, providing a broad spectrum of perspectives on the current state and potential of the area. These strategies collectively aim to capitalize on the identified strengths and opportunities while mitigating the weaknesses and threats. The ultimate goal is to elevate the Bili-Bili Reservoir's status as a tourist attraction and to make a meaningful contribution to the local economy. This research highlights the critical role of local community involvement in achieving sustainable development and underscores the potential of a holistic approach that synergizes cultural, social, and architectural elements. The findings and recommendations of this study offer valuable insights into achieving sustainable tourism growth, emphasizing the need for a balanced and integrated approach to the development of culinary tourism at the Bili-Bili Reservoir. This approach not only aims to boost tourism but also seeks to preserve and celebrate the unique cultural heritage of the Gowa Regency, ensuring that the development is both economically beneficial and culturally respectful.